Determination of lead content in the lime flower from Skopje by atomic absorption spectrometry - Kulevanova, Svetlana; Kadifkova-Panovska, Tatjana; Stafilov, Trajče; Lazaru, Ana (Macedonian Journal of Ecology and Environment, 1997)
The results from the investigation of lead content in lime flower collected from city of Skopje have been presented. Samples of lime flower (Tiliae flos) are collected from different localities in the city. Mineralization of the air-dried samples was performed by wet procedure. The content of lead was determined by Zeeman atomic absorption spectrometry. Obtained results pointed out that the concentration of lead in the samples originated from the more frequently part is several time over the concentration in those collected from the other localities. Concentration of lead in water extracts from certain samples is high and they are not recommended for preparation of common tea drinks.